2016
DOI: 10.1097/pec.0000000000000760
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Limited Head Computed Tomography in the Evaluation of Pediatric Ventriculoperitoneal Shunt Malfunction

Abstract: Our pilot study demonstrates that utilization of limited head CT scan in the evaluation of children with suspected VP shunt malfunction is a feasible strategy for the evaluation of the ventricular size. Further prospective and multidisciplinary studies are needed to evaluate the reliability of limited head CT for the clinical evaluation of VP shunt malfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…36 Limited cranial CT scan techniques to decrease exposure in patients with a ventriculoperitoneal shunt have also been recently proposed. 39 Therefore, in our model, rather than eliminate the risk entirely, we decreased the risk of radiation-induced cancer to 7 per 10 000 as the lower limit in our sensitivity analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…36 Limited cranial CT scan techniques to decrease exposure in patients with a ventriculoperitoneal shunt have also been recently proposed. 39 Therefore, in our model, rather than eliminate the risk entirely, we decreased the risk of radiation-induced cancer to 7 per 10 000 as the lower limit in our sensitivity analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In our model, we assigned values (or utilities) to health outcomes using a standard Health Utilities Index scale ranging from 0 (death) to 1 (baseline health, assumed as perfect health for this hypothetical population). The Health Utilities Index is a 15-item questionnaire designed to ask the minimum number of questions required to classify a subject's 10%-50% Sensitivity of CT 32 -37 66% 53%-88% Specificity of CT 32 -37 87% 76%-96% Sensitivity of fsMRI 32,36,38 58% 51%-78% Specificity of fsMRI 32,36,38 93% 89%-98% Sensitivity of ONSD 16 -19 75% 61%-83% Specificity of ONSD 16 -19 32% 22%-38% Sensitivity of SS 33 -35, 37 19% 4%-30% Specificity of SS 33 -35, 37 95% 91%-98% Probability of death and/or missed diagnosis a 0.1% (1:1000) 0.01%-0.2% Probability of radiation-induced malignancy 9,11,21,31,39 0.22% 0.07%-0.6%…”
Section: Utilitiesmentioning
confidence: 99%
“…A pediatric head CT scan is often used to assess the increase in ventricular size, an indication of VPS malfunction. 17 An alternative method for achieving this is MRI, which can provide acceptable images for diagnosing VPS malfunction in pediatric patients. 18 Margaret et al suggested that MRI scans should be used more often in the diagnosis of VPS malfunction, as they do not require radiation exposure, unlike CT scans.…”
Section: Discussionmentioning
confidence: 99%
“…The VPS is the most commonly used shunt in selected patients with hydrocephalus. 1 , 4 , 5 The VPS has been modified over the years. However, the current VPS comprises 3 parts: proximal (ventricular) catheter, pressure-sensitive valve with a reservoir, and distal (peritoneal) catheter.…”
Section: Discussionmentioning
confidence: 99%
“…A pressure-sensitive valve could be fixed or adjustable. 5 Although VP shunting is well known as one of the oldest procedures in neurosurgery practice, complication rates of VP shunting are 25%–60%. 1 …”
Section: Discussionmentioning
confidence: 99%